Simultaneous Upregulation of Elastolytic and Elastogenic Factors Are Necessary for Regulated Collateral Diameter Expansion - Andraska, Elizabeth; Skirtich, Nolan; McCreary, Dylan; Kulkarni, Rohan; Tzeng, Edith; McEnaney, Ryan (Frontiers in Cardiovascular Medicine, 2022)
Background: During arteriogenesis, outward remodeling of the arterial wall expands luminal diameter to produce increased conductance in developing collaterals. We have previously shown that diameter expansion without loss of internal elastic lamina (IEL) integrity requires both degradation of elastic fibers and LOX-mediated repair. The aim of this study was to investigate the expression of genes involved in remodeling of the extracellular matrix (ECM) using a model of arteriogenesis. Methods: Sprague-Dawley rats underwent femoral artery ligation with distal arteriovenous fistula (FAL + AVF) placement. Profunda femoral arteries (PFA) were harvested for analysis at various time points. Serum desmosine, an amino acid found exclusively in elastin, was evaluated with enzyme-linked immunosorbent assay (ELISA) as a marker of tissue elastolysis. Tissue mRNA isolated from FAL + AVF exposed PFAs was compared to the contralateral sham-operated using qPCR. HCAECs were cultured under low shear stress (8 dyn·s/cm2) for 24 h and then exposed to high shear stress (40 dyn·s/cm2) for 2–6 h. Primers used included FBN-1, FBN-2, Timp-2, LOX-1, Trop-E, Cath-K, Cath-S, MMP-2, MMP-9, FBLN-4, and FBLN-5 and were normalized to GAPDH. mRNA fold changes were quantified using the 2-ΔΔCq method. Comparisons between time points were made with non-parametric ANOVA analysis with Bonferroni adjustment. Results: PFAs showed IEL reorganization during arteriogenesis. Serum desmosine levels are significantly elevated at 2 days and one week, with a return to baseline thereafter (p < 0.01). Expression of ECM structural proteins (FBN-1, FBN-2, FBLN-4, FBLN-5, Tropoelastin, TIMP-2, LOX-1) and elastolytic proteins (MMP-2, MMP-9, Cathepsin S, Cathepsin K) exhibited an early peak (p < 0.05) relative to sham PFAs. After two weeks, expression returned to baseline. HCAECs demonstrated upregulation of FBN-2, FBLN-5, LOX-1 and Trop-E at 4 h of high shear stress, as well as elastolytic protein MMP-2. Conclusions: Elastin degradation begins early in arteriogenesis and is mediated by local upregulation of elastolytic genes. Elastolysis appears to be simultaneously balanced by production of elastic fiber components which may facilitate stabilization of the IEL. Endothelial cells are central to initiation of arteriogenesis and begin ECM remodeling in response to altered shear stress.